A bibliometric analysis of the neurotoxicity of anesthesia in the developing brain from 2002 to 2021 - Cao, Ying; Sun, Yang; Liu, Xiao; Yu, Kang; Gao, Danyang; Yang, Jiaojiao; Miao, Huihui; Li, Tianzuo (Frontiers in Neurology, 2023)
Background The neurotoxicity effects of anesthetic exposure on the developing brain have been one of the current research hotspots and numerous articles were published in the past decades. However, the quality and comparative information of these articles have not been reported. This research aimed to provide a comprehensive overview of the current state of the field by investigating research hotspots and publication trends concerning the neurotoxicity of anesthesia in the developing brain. Materials and methods On 15 June 2022, we searched articles on the neurotoxicity of anesthesia in the developing brain through the Science Citation Index databases from 2002 to 2021. Data of the author, title, publication, funding agency, date of publication, abstract, type of literature, country, journal, keywords, number of citations, and research direction were collected for further analysis. Results We searched and analyzed 414 articles in English on the field of neurotoxicity of anesthesia in the developing brain from 2002 to 2021. The country with the largest number of publications was The United States (US) (n = 226), which also had the largest total number of citations (10,419). Research in this field reached a small peak in 2017. Furthermore, the largest number of articles were published in three journals, Anesthesiology, Anesthesia and Analgesia, and Pediatric Anesthesia. The top 20 articles that were cited most often were studied. In addition, the top hotspots of this area in clinical investigations and basic research were analyzed separately. Conclusion This study provided an overview of the development in the neurotoxicity of anesthesia in the developing brain using bibliometric analysis. Current clinical studies in this area were mainly retrospective; in the future, we should place more emphasis on prospective, multicenter, long-term monitoring clinical studies. More basic research was also needed on the mechanisms of neurotoxicity of anesthesia in the developing brain.